Islamic Health Promoting University (I-HELP U): Case study of nutrition intervention program institutionalization at a university level - Imas Arumsari; Elia Nur Ayunin; Ony Linda (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
The Islamic Health Promoting University (I-HELP U) is an initiative program by Universitas Muhammadiyah Prof. DR. HAMKA as a health promotion program integrating both health and Islamic values. The pilot programs were implemented between September – November 2021. This study aimed to evaluate I-HELP U’s pilot programs, which consist of need assessment, health literacy, advocacy, and healthy behavior practices. The needs assessment was conducted to assess the baseline data of nutritional status and unhealthy lifestyles. Health literacy was performed to improve nutrition knowledge among participants. Advocacy was implemented to assist the production of regulation documents to support the program. Healthy behavior practices were implemented to improve the health-promoting behavior among participants. The results show that there were improvements in targeted outcomes on the initiative (policy documents establishment), participation (1,904 respondents of needs assessment, 300 participants in webinars, and 1,700 YouTube views), and knowledge level (p<0.05). The university leaders show a strong commitment in the policy-making to support I-HELP U since UHAMKA holds a vision to be a prophetic teaching university. This basic value supports the effort of I-HELP U to institutionalize the programs since it integrates Islamic values in the content. Future dissemination of the programs and regulations should be provided massively to all university academic communities.